Recent Advances on the Anti-Inflammatory and Antioxidant Properties of Red Grape Polyphenols: In Vitro and In Vivo Studies - Thea Magrone; Manrico Magrone; Matteo Antonio Russo; Emilio Jirillo (Antioxidants, 2019)
In this review, special emphasis will be placed on red grape polyphenols for their antioxidant and anti-inflammatory activities. Therefore, their capacity to inhibit major pathways responsible for activation of oxidative systems and expression and release of proinflammatory cytokines and chemokines will be discussed. Furthermore, regulation of immune cells by polyphenols will be illustrated with special reference to the activation of T regulatory cells which support a tolerogenic pathway at intestinal level. Additionally, the effects of red grape polyphenols will be analyzed in obesity, as a low-grade systemic inflammation. Also, possible modifications of inflammatory bowel disease biomarkers and clinical course have been studied upon polyphenol administration, either in animal models or in clinical trials. Moreover, the ability of polyphenols to cross the blood−brain barrier has been exploited to investigate their neuroprotective properties. In cancer, polyphenols seem to exert several beneficial effects, even if conflicting data are reported about their influence on T regulatory cells. Finally, the effects of polyphenols have been evaluated in experimental models of allergy and autoimmune diseases. Conclusively, red grape polyphenols are endowed with a great antioxidant and anti-inflammatory potential but some issues, such as polyphenol bioavailability, activity of metabolites, and interaction with microbiota, deserve deeper studies.